2010
DOI: 10.1103/physrevc.81.045804
|View full text |Cite
|
Sign up to set email alerts
|

Unified description of neutron superfluidity in the neutron-star crust with analogy to anisotropic multiband BCS superconductors

Abstract: The neutron superfluidity in the inner crust of a neutron star has been traditionally studied considering either homogeneous neutron matter or only a small number of nucleons confined inside the spherical Wigner-Seitz cell. Drawing analogies with the recently discovered multi-band superconductors, we have solved the anisotropic multi-band BCS gap equations with Bloch boundary conditions, thus providing a unified description taking consistently into account both the free neutrons and the nuclear clusters. Calcu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 51 publications
5
66
0
Order By: Relevance
“…This neutron contribution is enormous and will always dominate in the layers where neutrons are normal. Once superfluidity sets in, however, C n V is strongly suppresssed and becomes negligible when the temperature is much lower than the critical temperature T n c [23,24]. Given the density dependence of the neutron 1 S 0 gap there are only two regions, just above the neutron drip point and possibly in the deepest part of the crust, where C n V is relevant (see, e.g., Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This neutron contribution is enormous and will always dominate in the layers where neutrons are normal. Once superfluidity sets in, however, C n V is strongly suppresssed and becomes negligible when the temperature is much lower than the critical temperature T n c [23,24]. Given the density dependence of the neutron 1 S 0 gap there are only two regions, just above the neutron drip point and possibly in the deepest part of the crust, where C n V is relevant (see, e.g., Ref.…”
Section: Discussionmentioning
confidence: 99%
“…While the existence of two weakly damped longitudinal modes is unique to the superfluid phase, entrainment is fairly insensitive to superfluidity provided the pairing gap ∆ ≪ µ n [21], which is the case in most of the inner crust [22][23][24].…”
Section: Low-energy Dynamics Of the Neutron-star Inner Crustmentioning
confidence: 99%
“…Including such correlations the sequence of Wigner-Seitz (WS) cells is remarkably modified compared to the original one proposed by Negele and Vautherin [14]. Several authors have done calculations in this system using nonrelativistic functionals and with zero-range pairing interactions [6][7][8][9][10] or finite range pairing interactions [11,12], but without performing a systematic comparison among the two.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with the full band theory [22,23] has shown that the WS approximation can reproduce well ground-state properties of the outermost regions of the inner crust. Its validity in the regions closer to the star core, where the clusters nearly touch each other, is still under debate.…”
Section: Introductionmentioning
confidence: 99%